Analisis Rasio Profitabilitas Basis Kas Dan Basis Akrual Terhadap Return Saham (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2019-2021) - Viky Mainnatul Millah; Fikri, Muhammad Ali; Suryantara, Adhitya Bayu (Jurnal Riset Mahasiswa Akuntansi, 2024)
This study aims to analyzw the differences between cash-bases and accrual-bassed profitability rations on stock return in manufacturing companies listed on the Indonesia Stock Exchange. This study uses ROA (Return On Equity), ROE (Return On Equity) and ROI (Return On Investement) as profitability variabels. The data used were collected from 153 manufacturing compies over a periode of 3 years (2019-2021) and analyses using liniear regression. The results show that accrual-based RPE from alla the profitability variables used has a positive impact on stuck return. Others variabels, such as ROA and ROI, whether cash-based or accrual-bassed, do not have an impact. According to this study, the equiy performance of an organization, which can be measured by accrual ROE, plays a significant role in.